The effectiveness of Borneo Textile Corporation Sdn Bhd`s promotion strategy towards customer purchase decisions / Nazratul Radiah Duyok - Duyok, Nazratul Radiah (2008)
First, the research is about the effectiveness of Borneo Textiles Corporation Sein Bhd's Promotion Strategy towards Customer Purchase Decisions. The objective of the research is to determine the effectiveness of Borneo Textiles Corporation promotion strategy, to provide recommendation to further improve Borneo Textiles Corporation and to determine factors that influence customer to buy Borneo Textiles Corporation Sdn Bhd product. A research study indicates that the factors such as Advertising, Sales Promotion, Personal Selling and Public Relations of the Borneo Textile Corporation Sdn Bhd influence customer towards purchase Borneo Textile corporation Sein Bhd product and services. When conducting this research, the researcher made a questionnaire which consists of 30 questions that include student's background. Then, the researcher distributes it to I 00 respondents. In this research, the researcher only focuses in Kota Kinabalu area which includes Emadira, Kain Mewah and Mini Kain Mewah Complex. After collecting the entire questionnaire, the researcher then key in all the data into the SPSS software version I 2.0 for windows to analyze all the data that the researcher had collected. Finally, the researcher provides a final report which consists of the findings. This is the complete report that determines the problem, literature review, the researcher limitation on completing the report, the data and etc.